Chapter Le origini della politica migratoria italiana nel contesto europeo e mediterraneo: il nesso nazionale-internazionale in una prospettiva storica - PAOLI, SIMONE (Studi e saggi, 2021)
The chapter analyses the phase of definition of Italian policy making on migration between the mid 80's and the mid 90's. It aims to shed light on the interplay between national and international variables responsible for the definition of key choices made by the Italian political class in the field of migration regulation. The study makes use of a historical perspective, that is suitable to underscore this relationship at the Mediterranean and European level.